Louis-Patrick Bergot, Apocalypse et littérature au Moyen Âge. Réception de l’imaginaire apocalyptique dans la littérature française des xiie et xiiie siècles - Louis-Patrick Bergot (Perspectives Médiévales)
Of the many apocalypses composed during Judeo-Christian antiquity, only the Apocalypse of John and the Apocalypse of Paul (through the intermediary of the Vision of Saint Paul) have benefited from translations into Old French. Their textual reception is the subject of an exhaustive classification and a detailed study in this thesis. Because of their success, these two apocalypses left a lasting imprint on medieval mentalities, for they responded to two major concerns : the collective Judgment (Johannine Apocalypse) and the individual Judgment (Pauline Apocalypse). They gave rise to an imaginary world whose traces can be found in French medieval literature thanks to an intertextual approach. Several parts of medieval literature resort to this imaginary, whether it be visionary literature (with The Vision of Tondale and The Purgatory of Saint Patrick), allegorical literature (in The Tournament of the Antichrist and The Romance of the Rose) or didactic and religious literature (in La Somme le roi, the sermons or the stuffed epistles). The apocalyptic imaginary thus impregnates a considerable part of the literature of this time, so that one can consider it as an autonomous mental universe, rich of motives, places, creatures, and sometimes of anxieties. From text to text, this imaginary world has spread through intertextual strata that philology is able to distinguish. But this complex network of interferences should not make us forget that the reception of the apocalyptic imaginary is not only apprehended on a textual scale : it also brings into play cognitive mechanisms such as comprehension, representation or imagination.